Stay with Me: Uncertain Indices and Attentional Presence in Chat Interfaces - Bak Herrie, Maja; Zacher Søresen, Mette-Marie (The Nordic Journal of Aesthetics, 2023)
In this article, Herrie and Sørensen examine the mediation of typing indicators (“…”) in online messaging. Their point of departure is a scene from the contemporary novel Exciting Times by Naoise Dolan (2020), in which the ‘dots’ play a prominent role. Their analysis shows how typing indicators, as interface design, mediate the complex communication situation in which they take part: from being mere signals, they have slipped into our emotional lives. From a semiotic perspective (Charles S. Peirce), the authors define typing indicators as uncertain indices which through unknowability and suspense establish an attentional presence. In continuation hereof, the authors argue that the acts of writing and waiting in contemporary attentional ecologies (Yves Citton) through the mediation of typing indicators as indicators of attentional presence, could be considered a mode of caring (Bernard Stiegler).